2013
DOI: 10.1002/dmrr.2441
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor‐alpha infusion produced insulin resistance but no change in the incretin effect in healthy volunteers

Abstract: In healthy young male volunteers, acute systemic inflammation induced by infusion of TNF-α is associated with insulin resistance with no change in the incretin effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
1
11
1
Order By: Relevance
“…In agreement with previous reports (3)(4)(5)8), the infusion of TNF-␣ at high doses was accompanied by systemic inflammation with fever, malaise, and discomfort in all subjects. In vivo studies also show that TNF-␣ infusion can induce insulin resistance (3-5) but is not likely to affect glucose-stimulated insulin secretion (8).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous reports (3)(4)(5)8), the infusion of TNF-␣ at high doses was accompanied by systemic inflammation with fever, malaise, and discomfort in all subjects. In vivo studies also show that TNF-␣ infusion can induce insulin resistance (3-5) but is not likely to affect glucose-stimulated insulin secretion (8).…”
Section: Discussionsupporting
confidence: 92%
“…Glucose tolerance depends on insulin sensitivity and insulin secretion. We (3) and others (4,5) have shown that high physiological levels of TNF-␣ reduce insulin sensitivity in vivo. TNF-␣ also reduces glucose-stimulated insulin secretion, at least in vitro (6,7), whereas a human in vivo study reported reduced basal insulin levels with no effect on glucose-stimulated insulin secretion (8).…”
Section: Discussionmentioning
confidence: 89%
“…Acute exposure to TNF-a increased GLP-1 secretion from human NCIH716 EECs; however, GLP-1 levels were not increased in mice after acute TNF-a injection (4 mg/kg) (Kahles et al, 2014), nor in healthy, young male human subjects after 4-6 hr of intravenous TNF-a infusion (1 mg/m 2 body surface area per hr), a dose that produces circulating TNF-a levels of $30 pg/mL (Lehrskov-Schmidt et al, 2015;Nielsen et al, 2013). In contrast, chronic exposure to TNF-a inhibited GLP-1 secretion from EECs in vitro, whereas administration of the TNF-a blocker, etanercept, to high-fat-diet-fed mice improved the secretion of GLP-1 from primary murine EEC cultures derived from the etanercept-treated mice ex vivo (Gagnon et al, 2015).…”
Section: Glp-1: a Target And Mediator Of The Inflammatory Responsementioning
confidence: 98%
“…Additionally, glucose normalisation with insulin treatment also improves β-cell function and the incretin effect in type 2 diabetes [ 16 18 ]. Furthermore, clinical studies by our group demonstrate that systemic inflammation induced by tumour necrosis factor (TNF)-α infusion impaired the suppression of GLP-1 on endogenous glucose production [ 19 ], but did not change the incretin effect [ 20 ], in healthy humans. These findings suggest that the incretin effect may become impaired in critical illness as a consequence of hyperglycaemia rather than inflammation per se.…”
Section: Introductionmentioning
confidence: 99%